2007
DOI: 10.2135/cropsci2006.10.0688
|View full text |Cite
|
Sign up to set email alerts
|

Marker‐Assisted Introgression of Resistance to Cassava Mosaic Disease into Latin American Germplasm for the Genetic Improvement of Cassava in Africa

Abstract: The gene pools for breeding cassava (Manihot esculenta Crantz) in Africa currently contain only a fraction of the existing genetic variation found in Latin America where the crop originates. Our research aimed to broaden the genetic base in Africa by introducing Latin American (LA) germplasm. The first set of introductions comprised sexual seeds that led to the evaluation of 20,032 seedlings in Nigeria between 1990 and 1994. A second set comprised in vitro cultures, where the dominant CMD2 gene for cassava mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
82
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 16 publications
3
82
1
Order By: Relevance
“…In another study, Okogbenin et al (2007) made a first introduction of the germplasm from Latin America in Africa with materials from crosses between elite parental from breeding programs and a second introduction of material that was selected based on MAS (two microsatellites and six SCARs) and a subsequent evaluation of genotypes under natural conditions in a field that was infested with CMD in Nigeria. In the first set of entries, there was a devastating effect of the disease, infecting 100 % of the plants one month after planting.…”
Section: Mas Implementation For Cmd Resistancementioning
confidence: 99%
See 4 more Smart Citations
“…In another study, Okogbenin et al (2007) made a first introduction of the germplasm from Latin America in Africa with materials from crosses between elite parental from breeding programs and a second introduction of material that was selected based on MAS (two microsatellites and six SCARs) and a subsequent evaluation of genotypes under natural conditions in a field that was infested with CMD in Nigeria. In the first set of entries, there was a devastating effect of the disease, infecting 100 % of the plants one month after planting.…”
Section: Mas Implementation For Cmd Resistancementioning
confidence: 99%
“…In fact, the introduction of the CMD2 gene into various germplasm seems to be the most effective strategy in CMD control, as the incorporation of the CMD1 gene into exotic germplasm and subsequent field testing in Africa indicated that the incorporation of CMD1 has not been effective because this is a gene of minor quantitative effect (Fregene et al, 2006;Okogbenin et al, 2007). Moreover, the use of the dominant CMD2 gene has been successful in transferring gene resistance genotypes originally from Latin America (Okogbenin et al, 2007).…”
Section: Mas Implementation For Cmd Resistancementioning
confidence: 99%
See 3 more Smart Citations